A review of the genus Labeo (Teleostei: Cyprinidae) in Sri Lanka - Sudasinghe, Hiranya; Ranasinghe, R.h. Tharindu; Goonatilake, Sampath De Alwis; Meegaskumbura, Madhava (Zootaxa, 2018)
The taxonomy of the three native taxa assigned to the genus Labeo (L. dussumieri, L. fisheri and L. porcellus lankae) in Sri Lanka is reviewed. The population hitherto identified as L. dussumieri in Sri Lanka is shown to be a distinct species, here named L. heladiva. Labeo heladiva, new species, has a wide distribution in the low and mid-elevations of the island and is distinguished from its Indian congeners by the combination of having two pairs of barbels; 12–13 branched dorsal-fin rays; lateral line with 44–51 scales; ½8–½9+1+6–7 scales in transverse series; and 19–22 circumpeduncular scales. It differs from its closest relative, L. dussumieri, principally by having 44–51 vs. 50–60 lateral-line scales, 19–22 vs. 22–27 circumpeduncular scales, and by uncorrected pairwise genetic distances of 1.27–2.22% and 1.88–2.91% for the two mitochondrial genes COI and cytb, respectively. Labeo fisheri, which is endemic to the upper reaches of the Mahaweli River basin in the Knuckles mountain range and the central hills in the vicinity of Kandy, is distinguished from Indian congeners by having (in combination) only a single pair of barbels; dorsal fin with 10–12 branched rays; lateral line with 37–39 scales; 7+1+4½–6 scales in transverse series; and 17–20 circumpeduncular scales. Labeo lankae is recognized as a valid species endemic to Sri Lanka. Long suspected to have become extinct, or known only from spurious records, an extant population is reported from the northern dry zone of the island. Labeo lankae is the sister species of L. porcellus of peninsular India; it can be distinguished from its congeners by having, in combination, 10–12 branched dorsal-fin rays; 36–39 lateral-line scales; ½8+1+5–6½ scales in transverse series; and 21–24 circumpeduncular scales. It differs from L. porcellus principally by having ½8 (vs. ½6–½7) scales between the origin of the dorsal fin and the lateral line, 21–24 (vs. 20–21) circumpeduncular scales and uncorrected pairwise genetic distances of 1.27% and 1.41% for the mitochondrial genes COI and cytb, respectively. The three species of Labeo in Sri Lanka do not form a monophyletic group.